Gut Microbiota, Glucose, Lipid, and Water-Electrolyte Metabolism in Children With Nonalcoholic Fatty Liver Disease - Pan, Xiongfeng; Kaminga, Atipatsa C.; Liu, Aizhong; Wen, Shi Wu; Luo, Miyang; Luo, Jiayou (Frontiers in Cellular and Infection Microbiology, 2021)
There is evidence that nonalcoholic fatty liver disease (NAFLD) is affected by gut microbiota, glucose and lipid. However, the function of water-electrolyte metabolism remains undefined in children with NAFLD. Therefore, the aim of this case-control study was to better understand these interactions. The sample consisted of 75 children, aged between 7 and 16, of whom 25 had non-alcoholic fatty liver (NAFL), 25 had nonalcoholic steatohepatitis (NASH) and 25 were obese and without NAFLD. These groups were matched by age, sex, and body mass index. Data were collected between June, 2019 and December, 2019 at the Hunan children's Hospital, in China. Microbiome composition in fecal samples was assessed using 16S ribosomal RNA amplicon sequencing. In the clinical indices, 12 glucose and lipid metabolism indices were included, and 6 water-electrolyte metabolism indices were included. Interactions of gut microbiota, glucose, lipid and water-electrolyte metabolism were assessed using network analysis. The results indicated that microbiomes of NAFLD children had lower alpha diversity but higher beta diversity index than the other two groups. Specifically, anti-inflammatory and probiotics abundance (e.g. Faecalibacterium, Akkermansia, and Bifidobacterium_adolescentis) was significantly decreased in NAFLD, whereas the abundance of harmful bacteria (e.g. Staphylococcaceae) was increased. Moreover, the abundance of butyrate-producing bacteria (e.g. Faecalibacterium, Roseburia_inulinivorans, Roseburia_intestinalis and Coprococcus_comes) was significantly decreased in NASH. The abundance of these bacteria were associated with glucose, lipid and water-electrolyte metabolism (e.g. Glucose, Triglyceride, Cholesterol, inorganic salt, and total body water, etc.), implying that the NAFLD and its severity were associated with glucose, lipid and water-electrolyte metabolism dysbiosis. Therefore, these findings suggest that the gut microbiome, especially butyrate-producing bacteria, play an important role in the development of NAFLD in children.